2010
DOI: 10.1371/journal.pone.0012282
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of an Unusual Class I Myosin Involved in Vesicle Traffic in Trypanosoma brucei

Abstract: Myosins are a multimember family of motor proteins with diverse functions in eukaryotic cells. African trypanosomes possess only two candidate myosins and thus represent a useful system for functional analysis of these motors. One of these candidates is an unusual class I myosin (TbMyo1) that is expressed at similar levels but organized differently during the life cycle of Trypanosoma brucei. This myosin localizes to the polarized endocytic pathway in bloodstream forms of the parasite. This organization is act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 68 publications
6
33
2
Order By: Relevance
“…Five TbCAPs, TbHsc70, TbMyo1, TbCAP100 TbCAP116 and TbCAP118 were up‐regulated in BSF (Table ). Upregulation of TbMyo1 is consistent with Spitznagel et al where a threefold increase in the BSF was also observed. TbCAP161, TbCAP292 and TbCAP336 are expressed at equivalent levels in both life stages, while TbCAP125 and TbCAP186 are downregulated in BSF by twofold.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Five TbCAPs, TbHsc70, TbMyo1, TbCAP100 TbCAP116 and TbCAP118 were up‐regulated in BSF (Table ). Upregulation of TbMyo1 is consistent with Spitznagel et al where a threefold increase in the BSF was also observed. TbCAP161, TbCAP292 and TbCAP336 are expressed at equivalent levels in both life stages, while TbCAP125 and TbCAP186 are downregulated in BSF by twofold.…”
Section: Resultssupporting
confidence: 90%
“…TbCHC had the highest score and was recovered from all three experiments, as was the product of Tb11.01.3110 (TbHsc70), the ortholog of the clathrin uncoating ATPase of higher eukaryotes. The ORF Tb927.4.3380, which encodes myosin IB (TbMyo1) and is involved in endocytosis , as well as the ortholog of metazoan RME8 (Tb927.6.3500), which is involved in recycling of endocytic proteins , were both recovered from one of three independent experiments. No clathrin uncoating proteins or proteins homologous to auxilin for example were found; however for the latter there is no ortholog in the genome.…”
Section: Resultsmentioning
confidence: 99%
“…Endocytosis Assays-Endocytosis assays were performed with FITC-labeled tomato lectin as described previously (27). Briefly, nicotinamide-treated and untreated bloodstream trypanosomes (10 7 cells) were washed with PBS, centrifuged at 7000 rpm, and resuspended in 1 ml of free serum HMI-9 supplemented with 10 mg/ml of BSA containing tomato lectin-FITC conjugate (Sigma) at 20 g/ml.…”
Section: Methodsmentioning
confidence: 99%
“…clathrin and components of the actin cytoskeleton (26,27,34). However, the nicotinamide-induced morphological effects are apparent after 3 h, whereas in the case of RNAi cells, typically, inductions of 24 h or more are required for morphological pathologies to present themselves.…”
Section: Dicussionmentioning
confidence: 99%
“…brucei possesses two myosins belonging to classes I (TbMyo1) and XXI (TbMyo2). TbMyo1 is an unusual class I myosin that localizes to the polarized endocytic pathway in the bloodstream form and is evenly distributed throughout the procyclic form (insect from) [17]. Knockdown of TbMyo1 impacts on cell growth and morphology in the bloodstream but not in the procyclic form ( Figure 1) [17,18].…”
Section: Main Bodymentioning
confidence: 99%